A comparison of mitochondrial genomes from five species in three genera suggests polyphyly in the subfamily Achatinellinae (Gastropoda: Pulmonata: Stylommatophora: Achatinellidae). Issue 2 (3rd July 2018) - Price, Melissa R.; Forsman, Zac H.; Knapp, Ingrid; Toonen, Robert J.; Hadfield, Michael G.
Abstract: We compare the complete mitochondrial genomes of Achatinella fulgens, A. mustelina, A. sowerbyana, Partulina redfieldi, and Perdicella helena, five species of Hawaiian tree snails across three genera. Mitogenomes ranged in length from 15, 187 to 16, 793 base pairs, with a base composition of A (36.4–37.4%); T (42.2–42.7%); C (8.8–9.2%); and G (11.3–11.8%). Similar with other pulmonates, these mitogenomes contain 13 protein-coding genes, two ribosomal RNA genes, and 22 transfer RNA genes, with the order conserved among genera. Our study suggests polyphyly in the current arrangement of the subfamily Achatinellinae, part of a spectacular radiation in the Hawaiian Islands.